2022
DOI: 10.2147/iprp.s363079
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Community Pharmacists in Relation to Dispensing Antibiotics Without Prescription in Sudan: A Cross-sectional Study

Abstract: Background Dispensing antibiotics without prescription (DAwP) is a widespread practice, especially in developing countries, contributing to antibiotic resistance. Community pharmacists play a significant role in promoting rational use of antibiotics by refraining from DAwP, and providing drug information to patients. This study aimed to evaluate community pharmacists’ knowledge, attitude and practice, and to assess the factors behind DAwP. Methods A cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 22 publications
3
17
0
Order By: Relevance
“…Most of the antibiotics were purchased from pharmacies in several regions in Sudan [ 12 , 13 , 14 ]. This is compatible with the preceding report which revealed that more than 80% of the pharmacists in Sudan frequently dispense antibiotics without prescription [ 15 ].…”
Section: Introductionsupporting
confidence: 92%
“…Most of the antibiotics were purchased from pharmacies in several regions in Sudan [ 12 , 13 , 14 ]. This is compatible with the preceding report which revealed that more than 80% of the pharmacists in Sudan frequently dispense antibiotics without prescription [ 15 ].…”
Section: Introductionsupporting
confidence: 92%
“…Furthermore, age, gender, and years of experience were not significant factors for the level of knowledge similar to previous studies with gender and differed with experiences. 13 It resembled others with age, gender, and experiences. 17 A different finding reported by a cross-sectional survey evaluated pharmacist knowledge in Sri Lanka, revealing that higher education is related to higher awareness of antibiotic resistance.…”
Section: Discussionmentioning
confidence: 87%
“…11 Such deficient knowledge is an issue locally and in other countries. 11 Half of the responders agreed to use broad-spectrum antibiotics, and the patient can stop antibiotics when reliving the symptoms; the percentage of responders similar to one study 13 lower than in a previous study, 17,24 because it might they implemented antibiotics guidelines or more antibiotics uses awareness available. When antibiotic therapy is to be used, it should be targeted to the pathogen as far as possible.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations